Influence of assumed geometric and material imperfections on the numerically determined ultimate resistance of hot-rolled U-shaped steel members. (August 2018) - Beyer, André; Boissonnade, Nicolas; Khelil, Abdelouahab; Bureau, Alain
Abstract: In order to predict the ultimate resistance of members by means of numerical simulations (GMNIA – geometric and material non-linear analysis with imperfection), it is indispensable to realistically assume geometric and material imperfections. For I-shaped profiles, it is possible to find several studies concerning the influence of geometric (for example member out-of-straightness) and material imperfections (residual stresses) on the ultimate resistance of the member. However, the sensitivity of hot-rolled U-shaped members to geometric and material imperfections has not been addressed in detail before. Moreover, the research projects concerning hot-rolled U-shaped members performed in the past often assumed different forms of geometric imperfections and residual stresses. Sometimes one may even find contradictory recommendations concerning the form of the geometric imperfection to be applied to the member. Therefore, it seemed interesting and necessary to conduct a comprehensive study explicitly addressing the sensitivity of the ultimate resistance of U-shaped members on the assumption of the geometric imperfections and residual stresses. The results of this study are presented hereafter and recommendations on the form and amplitude of geometrical imperfections and residual stresses to be included into numerical simulations are derived. Highlights: An auto-equilibrated residual stress pattern is proposed for U sections. The influence of imperfections on the ultimate resistance of U-shaped members is studied. Recommendations on the imperfections to be used for GMNIA calculations of U-shaped members are derived.